Shame's Unwelcome Interruption and Responsive Movements Body, Religion, Morality - an Interdisciplinary Study - Henriksen, Jan-Olav (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"Shame is a deeply problematic emotion that causes much trouble and pain in our lives, interrupting our immediate mode of being in the world and making us feel bad about who we are. Nevertheless, we use it in many contexts to discipline others, impede personal development, regulate participation in communities, and instil in others commonly accepted norms and values. All these uses of shame suggest to some that it is a phenomenon with positive attributes, despite its darker sides. Many who study shame do so from the vantage point of a single scholarly discipline. This book is an exception. Its authors approach shame from multiple perspectives, seeking a more nuanced picture of its various roles in human life and its impact on social interaction. This book explores shame from an interdisciplinary perspective that looks into psychology, philosophy, evolutionary theory, theology and religious studies, and moral theory. The theoretical insights are then applied to understand shame's workings in relation to embodiment, religion, and morality. Hence, Shame's Unwelcome Interruption and Responsive Movements. Body, Religion, Morality - an Interdisciplinary Study will be of value to anyone who is interested in approaching shame from a comprehensive, scholarly perspective."